The Relationship between Financial Literacy Skills and Savings Behavior for Retirement: A Case Study of Kasikornbank Public Company Limited Section Business Network Head South 1 - Teeratansirikool, Luliya; Rattanavijit, Nalinda (Business Administration and Management Journal Review, 2025)
The objectives of this study are to analyze the level of financial literacy skills, retirement savings behavior, and the relationship between financial literacy skills and retirement savings behavior of Kasikornbank Public Company Limited Section Business Network Head South 1’s employee. This study covers all population totally 304. Questionnaires are the instrument for collecting the data. The statistical techniques used for analyze the data are frequency, percentage, means, standard deviations, and Pearson Correlation Coefficients. The findings of the study revealed that employees have high overall financial literacy skills. The behavior of savings for retirement is at the highest level. Furthermore, it was found that financial literacy skills had a positive correlation with retirement savings behavior at a statistically significant level of .05.